Area‐preservation Simplification of Polygonal Boundaries by the Use of the Structured Total Least Squares Method with Constraints. Issue 5 (6th February 2015) - Tong, Xiaohua; Jin, Yanmin; Li, Lingyun; Ai, Tinghua
Abstract This article presents an area‐preservation approach for polygonal boundary simplification by the use of structured total least squares adjustment with constraints (STLSC), with the aim being to maintain the area of the original polygons after the simplification. Traditionally, a simplified line is represented by critical points selected from the original one. However, this study focuses on maintaining the areas of the polygons in the process of simplification of polygonal boundaries. Therefore, the proposed method in this article is a supplement to the existing line simplification methods, and it improves the quality of the simplification of polygonal boundaries in terms of positional and area errors. Based on the sub‐divisions of the original polyline, using the critical points detected from the polyline by the use of line simplification methods, the framework of the proposed method includes three main components, as follows: (1) establishment of the straight‐line‐segment fitting model based on both the critical and intermediate points on the sub‐polyline; (2) introduction of both area and end‐point constraints to reduce the geometric distortions due to the line simplification; and (3) derivation of the solution of boundary simplification by the use of STLSC. An empirical example was conducted to test the applicability of the proposed method. The results showed that: (1) by imposing the linear fitting model on both the critical and intermediate points on the sub‐polylines in the proposed STLSC method, the positional differences between the original points and the simplified line are approximately in a normal distribution; and (2) by introducing both end‐point and area constraints in the proposed STLSC method, the areas of the simplified polygons are the same as those of the original ones at different scales, and the two neighboring fitted lines are connected to each other at the optimized position.